Fichte e a filosofia do espírito de Hegel (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The issue of this paper is to explore the relation between Hegel’s philosophy of spirit (erroneously taken for philosophy of mind by Anglo-american commentators) and Fichte’s philosophy of art and a philosophy of philosophy as they were developed by Fichte in the mid-1790’s.